Objective Self-Awareness in the Malay Context - Aknouche, Nadjet; MOHD. NOOR, Noraini
The present research aimed to explore objective self-awareness among Malays. 106 participants were asked to complete the Rosenberg self-esteem scale (Rosenberg, 1965), self-consciousness scale (Fenigstein, Scheier, & Buss, 1975), and actual-ideal self-discrepancy scale (Heine & Lehman, 1999) in the presence of a mirror, a camera, or an absence of both (mirror/camera). Findings indicated that while participants in front of a mirror reported significantly higher self-esteem than participants facing a camera or facing none of the two, no significant difference was found between the three conditions with respect to self-consciousness, and actual-ideal self-discrepancies.